Pendampingan Penyusunan Rencana Pengembangan Kawasan Permukiman (RPKP) Kecamatan Tanjung dan Kecamatan Pemenang - Pratama, Indah Arry; Lismaya Dewi, Ni Putu Ety; Malikah Hr, Baiq (Jurnal Pengabdian UNDIKMA, 2020)
The purpose of this service is to help the Lombok Utara Government in making plans to develop residental area, as a basis for managing cities without slum program.The object of this service is in Tanjung and Pemenang Subdistrict. Community service activities are generally carried out in 4 stages, that is: preparation stage, verification location and formulation of concepts and strategies, formulation of handling plans, and detail engineering desain.The result of community service is the form for developing residential areas plan document, can be used to prioritize the handling programs so that the planning become faster and more precise.